PERLINDUNGAN HUKUM TERHADAP ANAK NIKAH SIRI DARI PERSPEKTIF HUKUM POSITIF - Andri Wahyudi (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
Children are a mandate and gift from God Almighty, who has inherent dignity and worth as a complete human being whose rights must be protected without being discriminated against. The presence of children in a marriage is a joy and priceless. However, children from unregistered marriages or marriages that are not registered by the state have different legal protections from children from marriages registered by the state. The formulation of the problem in this study is how the law of unregistered marriage according to Positive Law and how the legal protection of children born from the result of unregistered marriage. In this study, the authors use library research methods, namely research that uses books as a source of data. In this case, the author conducts research by examining library materials, whether in the form of books, laws, journals, fiqh books, and other sources relevant to the formulation of the problem that will be studied by the author. Legal protection for children from unregistered marriages if viewed from the perspective of Positive Law, namely the status of the child does not have a father or child from outside of marriage and does not have a lineage to his father. The government should immediately amend all products of the Marriage Law to suit the appropriate conditions in society that protect all groups and interests.